Aberration‐Corrected Holographic Optical Elements Based on Consistent Shapes of Printed Hogels - Jiwoon Yeom; Jung Beom Choi; Geun Seop Choi; Kwang‐Soon Choi; Jisoo Hong (Advanced Photonics Research)
Herein, a holographic optical element (HOE) printing technique which maintains shapes and sizes of hogels across diverse focal positions, and aberration‐corrected HOEs which are fabricated by it are proposed. The proposed HOE printer employs nonpixelated focus modulators composed of double 4f optics in reference and signal beam paths to record hogels with the consistent shapes, which is validated via the ray tracing simulation. An optimization algorithm is developed for aberration‐corrected HOEs, dedicated to the proposed printing system. Imaging simulations verify the improved image quality compared to a baseline case by showing a 5 times sharper point spread function. As the experimental verification, a HOE printer is realized, which provides 1 × 1 mm of hogels consistently over 20° × 20° of angular ranges and 8 diopters of focal length changes. Displaying experiments using printed HOEs (mono‐colored and full‐colored ones) verify the proposed method with aberration‐corrected and see‐through images.